The Influence of Audit Quality, Public Accountant Firm Reputation, Audit Committee and Return On Assets Against Going Concern Audit Opinions in Consumer Goods Sector Companies Listed on the Indonesia Stock Exchange in 2015 - 2019 - Arie Pratania; Darwin; Elvina; Felicia (Jurnal Mantik, 2021)
The purpose of this research is to determine the effect of audit quality, reputation of public accounting firms, audit committee and return on assets on going concern audit opinion in consumer goods sector companies. This research uses associative research methods and this research approach uses quantitative methods. The sample of this research is consumer goods sector companies listed on the Indonesian stock exchange in 2015 - 2019. Data collection is used by collecting literature reviews and documentation. This analysis uses a multivariant analysis technique using logistic regression where the independent variable is a combination of metric and non-metric. The results of this study indicate that the quality of the audit, the reputation of the public accounting firm, and the audit committee have no effect on going concern audit opinion on consumer goods sector companies listed on the Indonesian stock exchange in 2015 - 2019.